THE SIGNIFICANCE OF PROPER COOLING TOWER WATER TREATMENT: A CASE STUDY - Mohd Nadzrie Ahmad, (INTERNATIONAL JOURNAL OF INNOVATION AND INDUSTRIAL REVOLUTION (IJIREV), 2024)
This paper presents the result of a study of the effect of cooling tower system in terms of performance and cost of maintenance. The study was conducted in a two-storey shopping complex building. Observation on site was held to obtain data on full load amp (FLA) and chilled water temperature (CWT) before and after servicing cooling tower unit. Energy of cooling tower were evaluated by analysis of FLA and CWT in percentage value. The condition on the system and component were also observed to differentiate the condition before and after treatment. The result obtained showed that cooling system performance after the treatment was increased.